Handbook of metallonutraceuticals (Taylor & Francis, 2014)
"Reviewing the health applications of selected metallic elements and the inorganic, organic, and bio-chemistry underlying the formulation of metallonutraceuticals, this comprehensive work provides a detailed description of the fundamentals and end-use applications of a series of metals vital to the metabolic and nutritional activities of human beings. Assuming a basic understanding of the role of metals in human physiology, it addresses various production issues including scaling up, processing, and automation from different scientific perspectives, as well as FDA regulations, institutional regulations, and ethics for industrial operations and corporate transactions"--Provided by publisher.
Keywords: Dietary supplements.; Trace elements.; elektronické knihy; electronic books